Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1002/mrd.10037
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally‐regulated changes of Xist RNA levels in single preimplantation mouse embryos, as revealed by quantitative real‐time PCR

Abstract: Xist RNA localizes to the inactive X chromosome in cells of late cleavage stage female mouse embryos (Sheardown et al., 1997: Cell 91:99-107). Fluorescence in situ hybridization (FISH), however, does not quantify the number of Xist transcripts per nucleus. We have used real-time reverse transcription-polymerase chain reaction (RT-PCR) to measure Xist RNA levels in single preimplantation embryos and to establish developmental profiles in both female and male samples. The gender of each embryo was readily establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 56 publications
6
53
1
Order By: Relevance
“…However, during the preimplantation period, X inactivation is a reversible dynamic process; both X-chromosomes are active after embryonic genome activation and XCI is not fully accomplished during early development, which leads to a higher expression of X-linked genes in female embryos (Kobayashi et al 2006, Bermejo-Alvarez et al 2010a. In this sense, a higher expression of selected X-linked genes such as XIST, glucose-6-phosphate dehydrogenase (G6PD), HPRT1, PGK, XIAP and MAOA was reported for mouse (Kay et al 1994, Hartshorn et al 2002, bovine (Gutierrez-Adan et al 2000, Peippo et al 2002, Wrenzycki et al 2002, Jimenez et al 2003, Morton et al 2007) and human (Taylor et al 2001) embryos. The developmental stage at which XCI is accomplished is not clear and may differ greatly between species (Okamoto & Heard 2009), but two global transcriptional studies reported that many X-linked genes are upregulated in female blastocysts in mice (Kobayashi et al 2006) and especially in cattle, where most of them (w90%) are highly expressed in females (Bermejo-Alvarez et al 2010a).…”
Section: Transcriptional Sexual Dimorphism In Preimplantation Embryosmentioning
confidence: 99%
“…However, during the preimplantation period, X inactivation is a reversible dynamic process; both X-chromosomes are active after embryonic genome activation and XCI is not fully accomplished during early development, which leads to a higher expression of X-linked genes in female embryos (Kobayashi et al 2006, Bermejo-Alvarez et al 2010a. In this sense, a higher expression of selected X-linked genes such as XIST, glucose-6-phosphate dehydrogenase (G6PD), HPRT1, PGK, XIAP and MAOA was reported for mouse (Kay et al 1994, Hartshorn et al 2002, bovine (Gutierrez-Adan et al 2000, Peippo et al 2002, Wrenzycki et al 2002, Jimenez et al 2003, Morton et al 2007) and human (Taylor et al 2001) embryos. The developmental stage at which XCI is accomplished is not clear and may differ greatly between species (Okamoto & Heard 2009), but two global transcriptional studies reported that many X-linked genes are upregulated in female blastocysts in mice (Kobayashi et al 2006) and especially in cattle, where most of them (w90%) are highly expressed in females (Bermejo-Alvarez et al 2010a).…”
Section: Transcriptional Sexual Dimorphism In Preimplantation Embryosmentioning
confidence: 99%
“…The FGF receptor family [14,15], IL6 and IL6r [16,17] are strongly expressed at the blastocyst stage and are known to play critical roles in postblastocyst development and implantation. Xist is required for X inactivation [18] and is also expressed strongly in the blastocyst stage [19][20][21]. The transcription level of Xist in female embryos was substantially higher than that of male embryos [19,21].…”
Section: Discussionmentioning
confidence: 99%
“…Xist is required for X inactivation [18] and is also expressed strongly in the blastocyst stage [19][20][21]. The transcription level of Xist in female embryos was substantially higher than that of male embryos [19,21]. It has been reported that in cattle these genes are useful markers for assessing the developmental potency of nuclear transfer embryos at the blastocyst stages [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breaching Lyon's hypothesis, marsupials (and maybe mice) preferentially inactivate the paternally derived X chromosome via an imprint (Takagi and Sasaki, 1975;Zuccotti and Monk, 1995). Mice are now thought to lose their paternal imprint after the first dozen rounds of embryonic cleavage, randomising inactivation during the differentiation of the inner cell mass (Hartshorn et al, 2002).…”
Section: Inactivationmentioning
confidence: 99%